EFEKTIVITAS PIJAT OKSITOSIN TERHADAP PENGELUARAN ASI PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS KARYA PENGGAWA TAHUN 2021 - iis utami (Universitas Aisyah Pringsewu, 2023)
Breast milk is a source of life for children which is very important in the first life of a child. Expression of breast milk can be accelerated by non-pharmacological action, namely through oxytocin massage. The purpose of this study was to determine the effectiveness of oxytocin massage on breastfeeding in Post Partum mothers at Public Health Center Karya Penggawa, Pesisir Barat Regency in 2021.The design of this study used True Experimental with a Randomize Control Trial (RCT) research design. The samples in this study were 30 respondents, 15 control groups and 15 intervention groups with purposive sampling. The instruments used were the observation sheet and SOP. The statistical test used the Chi Square test. The results obtained indicate that oxytocin massage has an effect on breastfeeding. Mothers who received oxytocin massage were 3.2 times more likely to express breast milk than mothers who received warm water compresses. Those who received oxytocin massage had an intensity of expressing breastmilk faster than those who did not. Mothers should pay more attention to the need for breast milk for their children and how to facilitate the release of breast milk as well as family support, especially husbands, which are very much needed.